Effect of Polysaccharides From Enteromorpha intestinalis on Intestinal Function in Sprague Dawley Rats - Li, Xia; Zhang, Miao; Khoo, Hock Eng; Jiang, Tiemin; Guan, Yuan; Li, Peijun (Frontiers in Pharmacology, 2022)
This study aims to determine the effect of polysaccharides extracted from Enteromorpha intestinalis (EI) on intestinal function of Sprague Dawley (SD) rats. The polysaccharides were extracted from the green alga using water and alkali, where these extracts were named WPEI and APEI, respectively. The dried powder of EI was labeled as DPEI. Proximate compositions, minerals, and amino acids of the DPEI, WPEI, and APEI were determined. The growth-promoting effect of the polysaccharides on selected intestinal microflora was determined based on the plate count method, whereas the in vivo effect of DPEI and its polysaccharides on the intestinal function of the SD rats was determined. These rats were fed with 1% WPEI, APEI, and DPEI. The result showed that APEI had lower total sugars and total proteins content than the WPEI. WPEI did not contain arabinose. The WPEI and APEI also had a better ability to promote microbial growth than the DPEI. The in vivo study showed that WPEI improved intestinal peristalsis and other intestinal functions compared with the other rat groups. The final body weight of the experimental rats treated with DPEI was also lower than the other groups. The pH value of the feces of all treated rats was lower than the control rats, and the moisture content of the fecal samples of these experimental groups was higher than the control group. Also, the intestinal activated carbon propulsion of the WPEI, APEI, and DPEI fed rats increased. Among the short-chain fatty acids content determined in the fecal samples, the propionic acid content of the WPEI group was significantly highest. Therefore, WPEI had the best effect in improving intestinal digestion.